Galectin-3 is a marker of myocardial and vascular fibrosis in Kawasaki disease patients with giant aneurysms. (15th December 2015) - Numano, Fujito; Shimizu, Chisato; Jimenez-Fernandez, Susan; Vejar, Matthew; Oharaseki, Toshiaki; Takahashi, Kei; Salgado, Andrea; Tremoulet, Adriana H.; Gordon, John B.; Burns, Jane C.; Daniels, Lori B.
Abstract: Backgrounds: Galectin-3 (Gal-3) is a multifunctional matricellular protein associated with heart failure and cardiovascular events. Gal-3 is required for transforming growth factor-β pathway-mediated myofibroblast activation that is a key process in coronary artery aneurysm formation in Kawasaki Disease (KD). Autopsies from young adults late after KD onset (AKD) have demonstrated bridging fibrosis throughout the myocardium and arteries. In this study, we postulated that Gal-3 may participate in the pathogenesis of myocardial and vascular fibrosis and the remodeling of coronary artery aneurysms following acute KD. Methods and results: We measured plasma Gal-3 levels in 63 pediatric KD (PKD) and 81 AKD subjects. AKD subjects with giant aneurysms had significantly higher Gal-3 levels compared to the other adult groups (all p < 0.05). All PKD groups had significantly higher Gal-3 levels than pediatric healthy controls (HC) (all p < 0.05). Histological and immunohistochemical staining was performed on tissues from 10 KD autopsies and one explanted heart. Gal-3 positive staining was detected associated with acute inflammation and in spindle-shaped cells in the myocardium and arterial wall in KD subjects with giant aneurysms. Conclusions: AKD subjects with giant aneurysms and PKD subjects had significantly higher plasma Gal-3 levels than HC and Gal-3 expression was increased in the myocardium of KD subjects who died with either acute inflammation or marked myocardial fibrosis. Gal-3 may be a clinically useful biomarker that identifies a subset of KD patients at highest risk of myocardial and vascular fibrosis, and may be an attractive therapeutic target to prevent myocardial dysfunction in this subset.